"Positive-negative-negative": a colloidal delivery system for bioactive compounds. (October 2020) - Sabet, Saman; Seal, Chris K.; Akbarinejad, Alireza; Rashidinejad, Ali; McGillivray, Duncan J.
Abstract: An uncommon "positive-negative-negative" (PNN) colloidal delivery system is made via depositing highly negatively-charged alginate onto the surface of a bilayer emulsion, where the primary and secondary layers are positively and negatively-charged, respectively. The physicochemical and oxidative stabilities, flow behavior, encapsulation efficiency and release profile of curcumin were investigated and compared to those of the primary emulsion and two bilayer emulsions using electrophoresis, light scattering, confocal microscopy, rheology, colorimetry, SPME headspace GC-MS, and UV–visible spectroscopy. At pH 7, the curcumin which was encapsulated using the PNN colloidal delivery system possessed the highest chemical stability compared to all systems tested, with, significantly, the lowest degradation rate per day. The PNN delivery system also showed the greatest physical stability over 21 days of storage period at pH 3 and 5. The PNN colloidal system showed a moderate shear-thinning behavior at pH 5 and 7, while following a typical Herschel-Bulkley flow model at pH 3. The PNN system showed the oxidative stability in the order: pH 7˃pH 5˃pH 3; with the highest oxidative stability at pH 5 compared to the other systems tested. The PNN colloidal delivery system also showed 98.6% encapsulation efficiency at pH 3, in addition to a significantly higher curcumin release kinetics at pH 7, compared to the other systems, indicating improved pH-triggered properties of this system. Overall, the findings of this study suggest that the "positive-negative-negative" system is a more effective pH-targeted delivery system, with higher physicochemical stability over 21 days of storage, than primary and common "positive-negative" bilayer emulsions. Graphical abstract: Image 1 Highlights: Positive-negative-negative (PNN) layers produce an effective delivery system. Curcumin stability in the PNN system was greater than in simpler emulsions. PNN system showed a better oxidative stability than other emulsion systems. PNN delivery system releases curcumin more efficiently than other emulsions. Bilayer emulsions may not preserve curcumin more than primary emulsions.